Predictors of long‐term outcomes greater than 10 years after cardiac resynchronization therapy implantation. (15th March 2020) - Patel, Divyang; Trulock, Kevin M.; Moennich, Laurie Ann; Kiehl, Erich L.; Kumar, Anirudh; Toro, Saleem; Donnellan, Eoin; Grimaldi, Adam; Baranowski, Bryan; Hussein, Ayman A.; Tarakji, Khaldoun G.; Cantillon, Daniel J.; et al.
Abstract: Background: Cardiac resynchronization therapy (CRT) is indicated in patients with medically refractory heart failure and wide QRS duration. While much is known about predictors of left ventricular (LV) remodeling after CRT implantation and short‐term mortality, limited data exist on long‐term outcomes after CRT placement. Methods: We retrospectively reviewed all patients undergoing CRT implantation at our center between 2003 and 2008 and examined mortality using institutional electronic records, social security death index, and online obituary search. We included only patients with preimplant echoes with LV ejection fraction (LVEF) 35% or below. Variable selection was performed using stepwise regression and models were compared using goodness‐of‐fit criteria. A final model was validated with the bootstrap regression method. Results: Out of the 877 CRT patients undergoing implantation during this time, 287 (32.7%) survived longer than 10 years. Significant ( P  < .05) predictors of survival in our multivariate model were age, left ventricular diastolic diameter, sex, presence of nonischemic vs ischemic cardiomyopathy, QRS duration, atrial fibrillation, BNP levels, and creatinine levels at the time of CRT implantation. A model using the odds ratios from these variables had a receiver operating curve with an area under the curve score of 0.816 (standard error, 0.019) at predicting survival or freedom from LVAD or heart transplant for longer than 10 years after CRT implantation. The specificity for factors 3 or above and 5 or above was 68% and 77%, respectively. Conclusion: A large proportion of patients are still alive 10 years after CRT implantation. Variables at the time of CRT implant can help provide prognostic information to patients and electrophysiologists to determine the long‐term benefit and survival of patients after CRT implantation.